FokI vitamin D receptor gene polymorphism and serum 25-hydroxyvitamin D in patients with cardiovascular risk - Nakhl, Sahar (Arch Med Sci Atheroscler Dis, 2019)
INTRODUCTION: The biological actions of vitamin D are mediated through vitamin D receptor (VDR). Numerous single-nucleotide polymorphisms (SNPs) in the VDR gene have been identified, and some have been associated with cardiovascular disease (CVD) risk factors. This study aims to evaluate the association of five SNPs in the VDR gene with 25-hydroxyvitamin D (25[OH]D) levels in patients with at least one CVD risk factor. MATERIAL AND METHODS: Genomic DNA was sequenced using standard Sanger methods for five VDR SNPs (BsmI rs1544410; ApaI rs7975232; Cdx2 rs11568820; TaqI rs731236; FokI rs2228570) in 50 Mediterranean subjects having hypovitaminosis D with at least one documented CVD risk factor, aged 18 years or more. The collected variables were serum levels of (25[OH]D), HbA(1c), fasting plasma glucose, triglycerides, LDL cholesterol, and total cholesterol. RESULTS: BsmI, ApaI, and TaqI were moderately to highly intercorrelated. Cdx2 was less frequent than expected. With respect to the number of mutations in FokI, levels of (25 [OH]D) were 11.2 ±5.5 ng/ml in the absence of mutations, 12.6 ±4.7 ng/ml in the presence of one mutation, and 16.5 ± 5.5 ng/ml in the presence of two mutations. CONCLUSIONS: FokI polymorphism is more frequent in subjects with cardiovascular risk factors than in the general Caucasian population.